Zirconium-catalysed N-acylation of lactams using unactivated carboxylic acids - Hulsbosch, Joris; Claes, Laurens; De Vos, Dirk E. (Tetrahedron letters, 2018)
[Display omitted] •New method for the catalytic N-acylation of lactams with carboxylic acids.•Screening of Lewis acid catalysts for N-acylation of pyroglutamic acid methyl ester.•Yields up to 97% were reached with 10 mol% Zr(propoxide)4.•Substrate scope was investigated; with 57–97% yield achieved.•The drug aniracetam can be produced in 84% yield. A large number of chemicals including surfactants, nootropic drugs and pesticides contain an N-acylated lactam moiety in their molecular structure. In this work, the direct, catalytic N-acylation of a number of lactams with various unactivated carboxylic acids is reported. Several Lewis acid catalysts were evaluated for their activity in the N-acylation of pyroglutamic acid methyl ester with palmitic acid; the highest activities were observed for zirconium-based catalysts. Yields of up to 97% were obtained utilising 10 mol% Zr(propoxide)4 in mesitylene at reflux temperature, but ZrOCl2·8H2O was determined as the most stable catalyst. The substrate scope was investigated and a number of lactam-carboxylic acid combinations were successfully converted into the desired products in 57–97% yield. This method provides an alternative synthetic pathway towards the drug aniracetam, which can be produced in 84% yield. A plausible catalytic mechanism is presented based on kinetic experiments.